Integration of Descending Command Systems for the Generation of Context-Specific Locomotor Behaviors - Kim, Linda H.; Sharma, Sandeep; Sharples, Simon A.; Mayr, Kyle A.; Kwok, Charlie H. T.; Whelan, Patrick J. (Frontiers in Neuroscience, 2017)
Over the past decade there has been a renaissance in our understanding of spinal cord circuits; new technologies are beginning to provide key insights into descending circuits which project onto spinal cord central pattern generators. By integrating work from both the locomotor and animal behavioral fields, we can now examine context-specific control of locomotion, with an emphasis on descending modulation arising from various regions of the brainstem. Here we examine approach and avoidance behaviors and the circuits that lead to the production and arrest of locomotion.